Ecological consequences of shifting the timing of burning tallgrass prairie - Towne, Gene; Craine, Joseph M. (My University, 2014)
In the Kansas Flint Hills, grassland burning is conducted during a relatively narrow window because management recommendations for the past 40 years have been to burn only in late spring. Widespread prescribed burning within this restricted time frame frequently creates smoke management issues downwind. A potential remedy for the concentrated smoke production in late spring is to expand burning to times earlier in the year. Yet, previous research suggested that burning in winter or early spring reduces plant productivity and cattle weight gain while increasing the proportion of undesirable plant species. In order to better understand the ecological consequences of burning at different times of the year, plant production and species abundance were measured for 20 years on ungrazed watersheds burned annually in autumn, winter, or spring. We found that there were no significant differences in total grass production among the burns on either upland or lowland topographic positions, although spring burned watersheds had higher grass culm production and lower forb biomass than autumn and winter burned watersheds. Burning in autumn or winter broadened the window of grass productivity response to precipitation, which reduces susceptibility to mid-season drought. Burning in autumn or winter also increased the phenological range of species by promoting cool-season graminoids without a concomitant decrease in warm-season grasses, potentially widening the seasonal window of high-quality forage. Incorporating autumn and winter burns into the overall portfolio of tallgrass prairie management should increase the flexibility in managing grasslands, promote biodiversity, and minimize air quality issues caused by en masse late-spring burning with little negative consequences for cattle production.
Citation: Towne EG, Craine JM (2014) Ecological Consequences of Shifting the Timing of Burning Tallgrass Prairie. PLoS ONE 9(7): e103423. doi:10.1371/journal.pone.0103423
Keywords: Grassland burning; Flint Hills; Tallgrass prairie; Smoke management